2018
DOI: 10.1590/0104-6632.20180353s20170024
|View full text |Cite
|
Sign up to set email alerts
|

HIGHLY EFFICIENT PRODUCTION OF L (+)-LACTIC ACID USING MEDIUM WITH POTATO, CORN STEEP LIQUOR AND CALCIUM CARBONATE BY Lactobacillus rhamnosus ATCC 9595

Abstract: The objective of this study was to optimize the composition of the fermentation medium through a Central Composite Rotational Design (CCRD) for the production of L (+)-latic acid (LA) using Lactobacillus rhamnosus ATCC 9595 and potato, corn steep liquor (CSL) and calcium carbonate as raw materials. A CCRD with three independent variables (potato flour (PF), CSL and CaCO 3 concentrations) was performed for a total of 17 treatments. Kinetic studies were conducted, and samples were taken at time intervals of 0 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…L. rhamnosus has been extensively studied for various applications particularly the use as probiotic against diarrhea and arthritis [28]. This bacterial species was commonly found to remarkable tolerance when exposing to the harsh acidic condition which is a typical condition in the stomach and digestive tract [29,30] and it has also been used in lactic acid production [10,31]. Regarding the fast-growing and highly optically pure L-lactic acid-producing capabilities, not only the application in L-lactic acid production, a newly isolated L. rhamnosus SCJ9 may provide the suitable characteristics for the use as a probiotic in the food and feed industries.…”
Section: Identification Of L-lactic Acid Producing Bacteriummentioning
confidence: 99%
See 1 more Smart Citation
“…L. rhamnosus has been extensively studied for various applications particularly the use as probiotic against diarrhea and arthritis [28]. This bacterial species was commonly found to remarkable tolerance when exposing to the harsh acidic condition which is a typical condition in the stomach and digestive tract [29,30] and it has also been used in lactic acid production [10,31]. Regarding the fast-growing and highly optically pure L-lactic acid-producing capabilities, not only the application in L-lactic acid production, a newly isolated L. rhamnosus SCJ9 may provide the suitable characteristics for the use as a probiotic in the food and feed industries.…”
Section: Identification Of L-lactic Acid Producing Bacteriummentioning
confidence: 99%
“…Pretreatment with cellulosic material has been found to cause several technical problems such as inhibition of the enzyme involved in cellulose hydrolysis by intermediate products. On the contrary, various biomass materials in the form of starch such as corn, cassava, potato, barley, and wheat have been used as carbon sources for the production of lactic acid [10][11][12]. In addition, starch-containing wastes have also been reportedly used as the main substrate for lactic acid fermentation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…De Cunha et al. [ 19 ] reported that Lacticaseibacillus rhamnosus ATCC 9595 could produce 183.8 g L –1 of lactic acid using 220 g L –1 of potato flour and 55 g L –1 of CSL. Although not mentioned in these reports, CSL contains a large amount of lactic acid, consisting of a mixture of l ‐lactic and d ‐lactic acids.…”
Section: Introductionmentioning
confidence: 99%
“…of CSL could reduce the concentration of yeast extract to 1 g L -1 in L-lactic acid fermentation from starch hydrolysate using Enterococcus faecalis RKY1. De Cunha et al [19] reported that Lacticaseibacillus rhamnosus ATCC 9595 could produce 183.8 g L -1 of lactic acid using 220 g L -1 of potato flour and 55 g L -1 of CSL. Although not mentioned in these reports, CSL contains a large amount of lactic acid, consisting of a mixture of L-lactic and D-lactic acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation